Pesticide Toxicity Profile: Hydrocarbon Fumigants - Frederick M. Fishel (EDIS)
This document provides a general overview of human toxicity, provides a listing of laboratory animal and wildlife toxicities and a cross reference of chemical, common and trade names of hydrocarbon fumigants registered for use in Florida. This document is PI-71, one of a series of the Pesticide Information Office, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published September 2005.